2013
DOI: 10.3390/ijms141224692
|View full text |Cite
|
Sign up to set email alerts
|

Importance of H-Abstraction in the Final Step of Nitrosoalkane Formation in the Mechanism-Based Inactivation of Cytochrome P450 by Amine-Containing Drugs

Abstract: The metabolism of amine-containing drugs by cytochrome P450 enzymes (P450s) is prone to form a nitrosoalkane metabolic intermediate (MI), which subsequently coordinates to the heme iron of a P450, to produce a metabolic-intermediate complex (MIC). This type of P450 inhibition, referred to as mechanism-based inactivation (MBI), presents a serious concern in drug discovery processes. We applied density functional theory (DFT) to the reaction between N-methylhydroxylamine (NMH) and the compound I reactive species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
5
18
0
Order By: Relevance
“…Again, this state will be significantly destabilized, as the N H distance becomes longer. State II may be less stable than I at the reactant state, because even though having an N H covalent bond will stabilize II, a single ET from the substrate to the a 2u orbital is not a facile process in our experience [43], although exceptional cases have been shown to exist [14,15,44].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Again, this state will be significantly destabilized, as the N H distance becomes longer. State II may be less stable than I at the reactant state, because even though having an N H covalent bond will stabilize II, a single ET from the substrate to the a 2u orbital is not a facile process in our experience [43], although exceptional cases have been shown to exist [14,15,44].…”
Section: Resultsmentioning
confidence: 95%
“…This seems to suggest that the ET and PT occur in a stepwise manner. However, as mentioned above, the ET process is usually not energetically favorable in P450 reactions and does not yield a stable intermediate for a stepwise mechanism [43]. Therefore, the ET and PT processes are regarded as effectively concerted.…”
Section: Resultsmentioning
confidence: 98%
“…Owing to the newly-formed hydrogen-bonding between O-H and N, dichotomous behaviors are encountered at the following step. The amino radical IM species could undergo either a traditional O-rebound process to yield hydroxylamine which has been deemed to be the precursor to oxime (Cerny and Hanzlik, 2005 ; Hirao et al, 2013b ), or a rapid ring-opening of the cyclopropyl group forming a C -centered radical species, which is essential for the enzyme inactivation and could be converted to 3HP via a further oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, one must use quantum mechanical methods such as DFT. In recent years, several research groups have reported DFT studies of P450 MBI (de Visser et al, 2004 ; Rydberg and Olsen, 2011 ; Hirao et al, 2012 , 2013a , b ; Taxak et al, 2012 , 2013a , b ).…”
Section: Applications Of Dftmentioning
confidence: 99%
“…More recently, Hirao et al investigated part of the MBI process caused by amine-containing drugs (Hirao et al, 2013b ). Amines are prone to form nitrosoalkane metabolic intermediates in P450-mediated metabolism, and the nitrosoalkanes form a quasi-irreversible metabolic-intermediate complex (MIC) to inhibit P450s (Scheme 6 ) (Hanson et al, 2010 ).…”
Section: Applications Of Dftmentioning
confidence: 99%